First record of Common Blackbird Turdus merula nests built in a reedbed. Issue 1 (2nd January 2020) - Czyż, Beata; Halupka, Lucyna; Czuchra, Monika
ABSTRACT: In May 2020, during our study on the breeding ecology of the Eurasian Reed Warbler Acrocephalus scirpaceus, we found two nests of Common Blackbird built within an unmanaged reedbed. The distance between the nests and dry land, overgrown by deciduous forest, was about 25 m. One of the nesting attempts was successful while the second was deserted during the incubation stage. To our knowledge this is the first record of Blackbirds nesting in reeds. This observation supports the notion of great flexibility of nest-site selection in this species. We conclude that Blackbirds use reedbeds as a nesting site more often, but such nests may be easily overlooked.